Immunomodulation and Immunotherapy for Patients with Prostate Cancer: An Up-to-Date Review - Nigel P. Murray (Biomedicines)
Immunotherapy alone or in combination with chemotherapy or radiotherapy is the frontline treatment for melanoma and lung cancer. However, its role in prostate cancer is usually as a fourth-line treatment. It is usually employed in patients with metastasis, after androgen blockade and chemotherapy. This article reviews the immunosuppressive effects of prostate cancer and possible uses of various types of immunotherapies. It also considers when would be the optimal time to employ this type of therapy.